การตรวจวัดคอปเปอร์(II) นิกเกิล(II) ซิงค์(II) และโคบอลต์(II) พร้อมกันด้วยตาเปล่าโดยใช้เทคนิคบัลค์ออปโทด - สุวิจักขณ์ สุดไทย (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
Nowadays, optical sensor for detection of metal ions contamination in water has become a hot research topic because of its convenient and reliable approach to monitor in daily applications without resorting to instrumental analysis. In this work, a proposed method of colorimetric sensor for naked-eye detection of Cu(II), Ni(II), Zn(II) and Co(II) in aqueous solution based on bulk optode technique was developed. The optode membrane was prepared by incorporating of 1-(2-pyridylazo)-2-naphtol (PAN) as an ionophore and a chromoionophore, potassium tetrakis(4-chlorophenyl) borate (KTpClPB) as a cation exchanger and bis(2-ethylhexyl)sebacate (DOS) as a plasticizer in a poly(vinyl chloride) (PVC) membrane. As the result, the membrane containing 0.7 to 1 mg of PAN responded to Cu(II), Ni(II), Zn(II) and Co(II) ions by changing color of membrane from yellow to purple, brown, orange and green, respectively. Under the optimum conditions, the proposed membrane displayed a concentration of Cu(II) Zn(II) and Co(II) ions was 0.1 mM and Ni(II) ion was 0.5 mM with 15 minutes of sensing process at pH 5 buffering by acetic acid/acetate. Notably, the simultaneous naked-eye detection of Cu(II) and Ni(II), Cu(II) and Zn(II), Cu(II) and Co(II), Cu(II) Ni(II) and Co(II) in an aqueous solution by using thiourea and ethylenediamine as masking agents under the optimum conditions was accomplished.